CFD simulation of droplet formation under various parameters in prilling process - Muhammad, A. (Trans Tech Publications Ltd, 2014)
A computational fluid dynamics (CFD) model is used to investigate the droplet formation and deformation under the influence of different parameters. Droplet breakup phenomenon depends on several factors such as viscosity, velocity, pressure difference, and geometry. The most important parameter for droplet breakup is the Weber number (We) which is the ratio of disrupting aerodynamics forces to the surface tension forces. Volume of fluid (VOF) model is used in present work to simulate the droplet breakup. This work presents the effect of liquid velocity, viscosity, and orifice diameters on droplet formation and breakup. Â© 2014 Trans Tech Publications, Switzerland.